Analisis DNA Menggunakan Metode PCR sebagai Alat Diagnosis Laboratorium Klinik - Pramai Sheila Eka Khoireina; Pramesti Listanto; Liss Dyah Dewi Arini (Pusat Riset dan Inovasi Nasional, 2026)
The development of molecular biology has significantly transformed clinical laboratory diagnostics, particularly through DNA analysis. One of the most widely used techniques is the Polymerase Chain Reaction (PCR), a DNA amplification method capable of rapidly, sensitively, and accurately multiplying specific genetic fragments. PCR has become an essential diagnostic tool for detecting infectious, genetic, and malignant diseases, even at early stages when the amount of target DNA is minimal. This article aims to analyze the role of PCR in DNA analysis as a diagnostic tool in clinical laboratories, including its working principles, advantages, and relevance in modern clinical practice. This study employs a literature review approach by examining various scientific sources such as international journals and molecular biology textbooks. The findings indicate that PCR offers high sensitivity and specificity compared to conventional methods, thereby improving diagnostic accuracy and accelerating appropriate therapeutic decisions. Therefore, PCR represents a crucial innovation in clinical laboratory diagnostics that significantly contributes to improving healthcare quality.